Vulnerable cildren : global challenges in education, health, well-being, and child rights - Agbényiga, DeBrenna LaFa; Hitchcock, Robert K.; Johnson, Deborah J. (Springer New York, 2013)
They are laborers, soldiers, refugees, and orphans. In areas of the world torn by poverty, disease, and war, millions of children are invisible victims, deprived of home, family, and basic human rights. Their chances for a stable adult life are extremely slim. The powerful interdisciplinary volume Vulnerable Children brings a global child-rights perspective to the lives of indigenous, refugee, and minority children in and from crisis-prone regions. Focusing on self-determination, education, security, health, and related issues, an international panel of scholars examines the structural and political sources of children's vulnerabilities and their effects on development. The book analyzes intervention programs currently in place and identifies challenges that must be met at both the community and larger policy levels. These chapters also go a long way to explain the often-blurred line between vulnerability and resilience. Key areas of coverage include: Dilemmas of rights-based approaches to child well-being in an African cultural context. Poverty and minority children's education in the United States: The case study of a Sudanese refugee family. The heterogeneity of young children's experiences in Kenya and Brazil. A world tour of interventions for children of a parent with a psychiatric illness. An exploration of fosterage of Owambo orphans in Namibia. UNICEF in Colombia: Defending and nurturing childhood in media, public, and policy discourses. Vulnerable Children is a must-have resource for researchers, graduate students, clinicians and professionals across a range of fields, including child and school psychology, social work, maternal and child health, developmental psychology, anthropology, sociology, social policy, and public health.